Evaluation of Polyciclic Aromatic Hydrocarbons in Water and Microplastics - José, Sílvia (2021)
Polycyclic Aromatic Hydrocarbons (PAHs) are a group of environmental contaminants, classified as potentially toxic, mutagenic and carcinogenic, being an important public health concern. In the present study, we assayed different samples of water (superficial water, groundwater and tap water) for five PAHs: pyrene (Pyr), 1-chloro-pyrene (1-ClPyr), 1-bromine-pyrene (1-BrPyr), benzo-a-anthracene (BaA) and 7-chloro-benzo-a-anthracene (7-ClBaA) by gas chromatography - mass spectrometry (GC-MS) after sample concentration by solid phase microextraction. The adsorption of most abundant PAHs (Pyr) by PET (polyethyleneterephthalate), HDPE (high density polyethylene), LDPE (low density PE), PP (polypropylene) and PS (polystyrene) particles with 4 mm diameter (microplastics) dispersed in freshwater was assessed by high pressure liquid chromatography (HPLC) after 3 and 30 days. Our data showed that, all types of plastic adsorbed Pyr without statiscally significant difference. Adsorption enhances Pyr stability contributing to its persistence /accumulation in the environment.